Alternative Forms of Care with a Special Focus on NGO BOSCO’s Model of Foster Care - PS, George; Selvi, G Anbu (Journal of Neonatal Surgery, 2025)
This article explores the landscape of alternative care for children in India, with a special focus on foster care as implemented by the NGO BOSCO. Grounded in the rights-based framework of child protection, the paper begins by categorizing various forms of care types – institutional, kinship, adoption and foster care. It highlights the global and national shift toward family-based alternatives, making institutional care a last resort. Drawing on both international frameworks and evolving Indian legal and policy mechanisms, such as the Juvenile Justice (Care and Protection of Children) Act, CARA guidelines, and the Mission Vatsalya scheme, the article examines how alternative care is being integrated into national child protection systems. Special attention is given to the cultural nuances of kinship care and the emerging relevance of foster care in India. The article then presents BOSCO’s grassroots model of foster care, showcasing the organization's structured processes in identifying suitable children and foster families, conducting rigorous assessments and training, ensuring smooth transitions, and ongoing monitoring. Through BOSCO’s experience, the article reflects on operational challenges, systemic gaps, and the potential of foster care as a viable alternative to institutionalization in the Indian context. The study underscores the need for strengthened community-based care models, enhanced support systems, and robust monitoring mechanisms to realize the vision of family-based care for every child in need.